HUBUNGAN LAMANYA PEMAKAIAN KONTRASEPSI SUNTIK DMPA DENGAN KEMBALINYA KESUBURAN PADA POST AKSEPTOR KB SUNTIK DMPA - Handayani, Rohmi; Fajarsari, Dyah; Suryani, Evi Sri (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2010)
The objective of the research is to know correlation between duration of using injectable depomedroxy progesterone acetate (DMPA) with return of fertility in women ex-user injectable DMPA .The research was conducted in April to August 2010. The kind research is analytic survey with design of research is cross sectional. Sample was taken with accidental sampling and sample had taken 50 women ex-user injectable DMPA. Data was analized using Pearson Correlation.The result of the study showed that there was no correlation between duration of using injectable depomedroxy progesterone acetate (DMPA) with return of fertility in women ex-user injectable DMPA with Ï value = 0,119. Â  Key words: duration of using DMPA, return of fertility